2017
DOI: 10.1186/s12915-017-0437-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual conflict explains the extraordinary diversity of mechanisms regulating mitochondrial inheritance

Abstract: BackgroundMitochondria are predominantly inherited from the maternal gamete, even in unicellular organisms. Yet an extraordinary array of mechanisms enforce uniparental inheritance, which implies shifting selection pressures and multiple origins.ResultsWe consider how this high turnover in mechanisms controlling uniparental inheritance arises using a novel evolutionary model in which control of mitochondrial transmission occurs either during spermatogenesis (by paternal nuclear genes) or at/after fertilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 58 publications
0
47
0
Order By: Relevance
“…More recent genome analysis of natural populations in C. reinhardtii and in another green alga, Ostreococcus tauri , reported that recombination is not rare in the chloroplast genome, suggesting the occurrence of biparental inheritance (Blanc‐Mathieu et al ., ; Hasan et al ., ). These patterns are concordant with the suggestion (Birky, ; Radzvilavicius et al ., ) that biparental inheritance of organelles is ancestral, serving to recombine organelle genomes, and that the selective degradation of minus (chloroplast) or plus (mitochondrial) genomes in C. reinhardtii evolved secondarily to achieve the advantages of uniparental inheritance.…”
Section: Discussionmentioning
confidence: 97%
“…More recent genome analysis of natural populations in C. reinhardtii and in another green alga, Ostreococcus tauri , reported that recombination is not rare in the chloroplast genome, suggesting the occurrence of biparental inheritance (Blanc‐Mathieu et al ., ; Hasan et al ., ). These patterns are concordant with the suggestion (Birky, ; Radzvilavicius et al ., ) that biparental inheritance of organelles is ancestral, serving to recombine organelle genomes, and that the selective degradation of minus (chloroplast) or plus (mitochondrial) genomes in C. reinhardtii evolved secondarily to achieve the advantages of uniparental inheritance.…”
Section: Discussionmentioning
confidence: 97%
“…the coexistence of different mitochondrial haplotypes in the same nuclear background, which has been shown to cause physiological dysfunction [18,19]. SMI thus prevents potential intergenomic conflicts [18][19][20][21]. A plausible consequence of SMI, however, is that it puts severe antagonist sex-linked constraints on the evolution of mitochondria, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in theory, the accumulation of male fertility-impairing mutations in the mtDNA sequence should in itself select for a variety of evolutionary mechanisms that offset the negative effects to males. Such mechanisms might include genetic adaptations that occasionally permit paternal leakage in transmission of mtDNA at conception, thereby enabling male-harming haplotypes associated with particular ancestral matrilines to be replaced (Kuijper et al 2015, Radzvilavicius et al 2017. Alternatively, the presence of male fertility-impairing mutations in the mtDNA should invoke selection on the nuclear genome for compensatory counter-adaptations able to restore male fertility (Beekman et al 2014, Connallon et al 2017.…”
Section: Theory Linking the Mitochondria To Male Fertilitymentioning
confidence: 99%